2D cracks analysis with symmetric Galerkin boundary element method - Xu, Kai (2008)
The practical applications of a Symmetric Galerkin Boundary Element Method (SGBEM) for multiple traction-free cracks, frictional contact and cohesive cracks problems is described in this thesis. Attention has been concentrated in deriving the formulations used for the analysis of these problems. For the analysis of 2D linear elastic crack problems, the direct SGBEM for multiple cracks problems is derived.